Design and Development of a 3D printed gripper - Pecioski, Damjan; Shaipi, Albion; Shishkovski, Dejan (IEEE, 2024)
Robotic manipulators are essential components in industrial automation systems. The working body of the manipulator or the gripper is an indispensable manipulator component when it comes to performing tasks with precision, speed and reliability. The gripper may be incorporated into the robot's overall design or added to its fundamental framework. The working environment conditions as well as the tasks that need to be completed and the objects that need to be manipulated dictate the design of the robot gripper. In this paper the authors present a low-cost 3D printed robotic gripper. The gripper is designed with a detachable mount which allows for use with different robots. Having an easily fabricable and exchangeable working element allows for flexibility and adaptability in the working process.
Keywords: Force measurement , Costs , Service robots , Force , Three-dimensional printing , Manipulators , Sensors , Grippers , Servomotors , Robots